P111 Azithromycin prescriptions in a teaching hospital–do we need to monitor for adverse effects?. (14th November 2013) - Rajagopalan, P; De wit, K; Barrett, J; Breen, R
Abstract : Introduction: Azithromycin appears to have an important role in management of a number of conditions including non-CF bronchiectasis and COPD but with possible adverse effects including hearing loss and liver dysfunction that necessitate appropriate patient monitoring. We have examined our use of azithromycin and how we screen for complications in our Chest clinics. Methods: Data was collected on all azithromycin prescriptions provided at the Chest Clinic in a large UK teaching hospital over a 12 month period commencing 30-1–2012. In those patients receiving long-term azithromycin (≥12 Months), we collected data on parameters including sputum microbiology, previous NTM, liver function tests (LFTs), audiology testing and Qtc interval recording. Results: 192 prescriptions corresponding to 112 patients were identified. 62 of 112 (56%) were prescribed long-term azithromycin. Bronchiectasis (60%), COPD(19%), asthma (8%), ILD(7%), Bronchiolitis and others (6%) were the variety of diseases for which Azithromycin was prescribed. 28% had pseudomonas colonisation. 51(46%) patients were prescribed long-term azithromycin. Of these, 21 (25%) had been on azithromycin for less than 12 months. Sixty eight (82%) patients on long-term azithromycin had had LFTs and 3(3.5%) had audiology testing in the preceding 12 months.21(25%)had documented ECGs with Qtc interval. No patients tested had hearing loss and no documented QTc prolongation. The other common side effect noticed was GI upset in 6 patients (5.6%). The dosing was mostly 250mg three times a week 103(92%) There was also 500mg three times a week in 20(18%) H.influenzae (42%)Staphylococcus aureus (21%)Moraxella catarrhalis (11%)coliform sp (10%). We identified no new NTM in our Cohort. Conclusion: Although formal monitoring in this cohort was patchy, Significant documented adverse effects in this cohort were rare and optimal practice for long-term management of azithromycin use remains to be established.